Effect of pimobendan in addition to standard therapy for heart failure on prevention of readmission in elderly patients with severe chronic heart failure. Issue 1 (15th April 2013) - Kawano, Hiroaki; Arakawa, Shuji; Satoh, Osami; Matsumoto, Yuji; Hayano, Motonobu; Nakatomi, Daisuke; Yamasa, Toshihiko; Maemura, Koji
<x xml:space="preserve">Abstract</x> Aim We evaluated the effect of pimobendan, a positive inotropic agent, in elderly patients with frequent readmission as a result of heart failure despite conventional therapy. Methods Pimobendan was given to five male patients with severe chronic heart failure (New York Heart Association class III–IV) (age range 69–89 years; mean 78 ± 8 years; ischemic cardiomyopathy in three cases, dilated cardiomyopathy in two cases) who required repeated admission for heart failure despite conventional therapy with angiotensin inhibitors, beta‐blockers, diuretics and anti‐arrhythmic agents. After the addition of pimobendan at a dose of 1.25–3.75 mg/day, we evaluated serum levels of brain natriuretic peptide (BNP), left ventricular ejection fraction (LVEF), septal e′ and left ventricular end‐diastolic diameter (LVDD) by echocardiography, as well as readmission rates for more than 2 years. Results The serum level of BNP significantly decreased after treatment with pimobendan, although its level returned to pretreatment levels after 2 years. LVEF significantly improved after the treatment, with the improvement continuing beyond the 2 years, although LVDD did not change after treatment. Septal e′ significantly improved after the treatment, although its level returned to pretreatment levels at 2 years after the treatment. Readmission rates significantly decreased for 2 years after the treatment, although one patient required cardiac resynchronization therapy for severe heart failure, and another patient required cardiac pacemaker implantation for sick sinus syndrome 2 years after adding pimobendan. Conclusions Pimobendan in conjunction with conventional therapy for heart failure decreases the readmission rate in elderly patients with severe heart failure for at least 2 years. Geriatr Gerontol Int 2014; 14: 109–114.